Economic Impact of Sugarcane in Indonesia: An Input-Output Approach - Hani Perwitasari; Jangkung Handoyo Mulyo; Sugiyarto Sugiyarto; Arif Wahyu Widada; Abi Pratiwa Siregar; Zaura Fadhliani (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2021)
Sugarcane revitalization is both a challenge and an opportunity in Indonesia. Demand for sugar tends to increase from year to year that fulfilled by domestic production and imports. Thus, it is necessary to increase domestic sugarcane competitiveness to balance national sugarcane production and consumption. This study’s objectives were (1) to determine the forward linkage and backward linkage of sugarcane in Indonesia, and (2) to know the output, income, and employment multiplier. The linkages and multipliers of sugarcane were calculated by the input-output analysis of 66 sectors from 1975 to 2005 by Statistics Indonesia (BPS). Estimation values for 2010, 2015, and 2020 are obtained from the linear forecasting method. T-test was used to compare linkages and multipliers between sugarcane and the average of all sectors in the economy. The results showed that the backward linkage, output, and employment multiplier of sugarcane were lower than the average of all sectors in the economy. Besides, the forward linkage of sugarcane was equal, and the income multiplier was higher than the average of all sectors in the economy.